تقنيات معالجة البيانات الضخم ة بين الواقع الرقمي وجدلية تفعيل الحكومة الذكية في الجزائر - بلبل, رياض; بوقرة, مبروك (University of Eloued جامعة الوادي, 2022)
The developments that governments have known in transferring their services over the Internet within what is known as e-government, thanks to the techniques of processing big data, as the most important pillar on which the digital government depends in its interactions with the new digital environment for the stages of the fourth industrial revolution. This study aroused the interest of highlighting the critical role when mining big data and relying on its outputs in the process of transition to e-government and then to smart government. Therefore, by using the descriptive analytical approach in general, the intellectual and scientific background of the literature of the study variables was presented. Relying on the Algeria data analysis report from the United Nations Department of Economic and Social Affairs, for the year 2020, about the Algerian government and the extent to which it uses data analysis techniques as part of attempts to transform it into a smart e-government, to improve the service of its citizens. It was concluded that the optimal use of big data would change the traditional concept of services and practices into fast, accurate and low-cost smart methods, which requires the development of strategies to keep pace with the transformations and developments resulting from the stage of intensive use of smart technologies.
Big data processing techniques between digital reality and the dialectic of activating the smart government in Algeria
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: البيانات الضخمة، الحكومة الإلكترونية، الحكومة الذكية، تكنولوجيا الرقمية، التحول الرقمي.; big data, e-government, smart government, digital technology, digital transformation.